PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PROGRAM MADRASAH DINIYAH DI SD NEGERI 1 PEJOGOL KECAMATAN CILONGOK KABUPATEN BANYUMAS - Nurfuadi Nurfuadi; Inayatul Farihah (Jurnal Penelitian Agama, 2018)
Abstract: Learning of Islamic Education aims to make a religion and good people, piety and noble in practicing Islamic religious values. Learning of religious education uses two kind, they are intrakurikuler and extracurricular activities. Madrasah Diniyah is one of learning of Islamic Education which is use extracurricular, and will applied in State Elementari school 1 Pejogol. The results of this study indicate that the learning of Islamic Religious Education of Madrasah Diniyah program in State Elementary school of 1 Pejogol, Cilongok, Banyumas. That shows there are three stages implemented, namely planning, implementation and evaluation. The methods of teaching uses by Madrasah Diniyah teachers lecture are, learning task method, question and answer method, singing and demonstration, sorogan and rote. The use of instructional media in Madrasah Diniyah program utilizes the existing facilities in class ie blackboard and markers, and uses al-Quran, Iqra or Islamic books brought by the students themselves. Keywords: Learning Islamic Religious Education, Madrasah Diniyah.